Designing The Model of Engaging Activities for Speaking Assessment by Minimizing Students’ Anxiety - Putri, Dwi Amalia; Bharati, Dwi Anggani Linggar; Mujiyanto, Januarius (Universitas Negeri Semarang, 2019)
In Indonesia, English is learned as a foreign language. Based on study done by Jannah & Fitriati (2016), students had some problems in speaking and one of major problem was anxiety. Students were anxious to speak in English. That situations is commonly found in foreign language class as described by Horwitz, Horwitz & Cope (1986). Moreover, in speaking assessment, students may feel more anxious and this feeling may hinder their speaking skill (Hewitt & Stephenson, 1978; Liu & Jackson, 2008; Wilson 2006; and Woodrow, 2006). This research aimed to design a model of student engaging activities for speaking assessment, specifically in procedure text. This study used the research and development design (R&D) to create an assessment handbook that provided some engaging activities for speaking assessment purpose. There were five phases in this research: defining, designing, developing, implementing and evaluating phase. The results of the research showed the model was not effective. It was obtained that the t-test was less than t table (0,167 < 1,697). Related to students’ anxiety level, however, most students had moderate level of anxiety in both experimental (19 students) and control groups (15 students).